Comparative analysis of propagation properties of ASFV Odintsvo 02/14 isolate in primary cell cultures - D. V. Sharypova; I. Yu. Zhukov; N. N. Vlasova; O. S. Puzankova; V. L. Gavrilova; A. S. Igolkin; N. V. Koropova; I. V. Zhbanova (Ветеринария сегодня)
Odintsovo 02/14 isolate of African swine fever virus was tested for its propagation properties in primary cell cultures with adding different sera to the nutrient medium. The test results showed that the virus propagation was the most successful in porcine bone marrow and porcine kidney cells when fetal bovine serum and FS FetalClone II, multipurpose serum substitute were added.